Respostas
respondido por:
1
teorema de Pitágoras
a=hipotenusa
b=cateto
c=cateto
a^2=b^2+c^2
x^2=(2V2)^2+(V10)^2
Cancele as raízes ao QUADRADAS (2) com a potência que é elevada a 2
x^2=4.2+10
x^2=8+10
x^2=18
x=V18
x=3V2
abraço!!
a=hipotenusa
b=cateto
c=cateto
a^2=b^2+c^2
x^2=(2V2)^2+(V10)^2
Cancele as raízes ao QUADRADAS (2) com a potência que é elevada a 2
x^2=4.2+10
x^2=8+10
x^2=18
x=V18
x=3V2
abraço!!
xjsi:
aqui em cuiaba tanbem e 23:05
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás